Improvement as the Foundation of Liberty: Locke on Labour, Equality, and Civic Membership - Kashiwazaki, Masanori (Locke Studies)

(untitled) (Western Libraries at The University of Western Ontario, 2021)
Locke’s egalitarianism is concerned with not only equality before law (both natural and civil) but also moral and civic equality among those who are treated unequally, according to social rank. He considered the labouring poor as moral equals, with respect to their contribution towards labour and the responsibility they are able and ought to take in their acts, although he also recognised that they often fail to do so. A key to Locke’s moral vision is the term “labour,” implying the use of the common faculties of humankind, with industry and pain, in the manner in which God, who had provided them with these faculties, intended them to do. Locke’s idea of industry, which represents the contribution and disposition every person should make and have, marks the break with the humanist ideal of civic virtue. He also replaced the Protestant dichotomy between ordinary and political callings by recognising common people as equal contributors to the common good.